Assembly of the 30S ribosomal subunit in vitro and in cells - Williamson, James (Henry Stewart Talks, 2008)
Bacterial ribosome biogenesis, The Nomura assembly map, RNA folding and protein binding, Single molecule fluorescence, The basis for cooperative assembly, Isotope pulse chase experiments, Protein binding kinetics, The assembly landscape